Minimal impact of a care pathway for geriatric hip fracture patients. Issue 8 (August 2018) - Panella, Massimiliano; Seys, Deborah; Sermeus, Walter; Bruyneel, Luk; Lodewijckx, Cathy; Deneckere, Svin; Sermon, An; Nijs, Stefaan; Boto, Paulo; Vanhaecht, Kris
Abstract: Background: Adherence to guidelines for patients with proximal femur fracture is suboptimal. Objective: To evaluate the effect of a care pathway for the in-hospital management of older geriatric hip fracture patients on adherence to guidelines and patient outcomes. Design: The European Quality of Care Pathways study is a cluster randomized controlled trial. Setting: 26 hospitals in Belgium, Italy and Portugal. Subjects: Older adults with a proximal femur fracture (n = 514 patients) were included. Methods: Hospitals treating older adults (>65) with a proximal femur fracture were randomly assigned to an intervention group, i.e. implementation of a care pathway, or control group, i.e. usual care. Thirteen patient outcomes and 24 process indicators regarding in-hospital management, as well as three not-recommended care activities were measured. Adjusted and unadjusted regression analyses were conducted using intention-to-treat procedures. Results: In the intervention group 301 patients in 15 hospitals were included, and in the control group 213 patients in 11 hospitals. Sixty-five percent of the patients were older than 80 years. The implementation of this care pathway had no significant impact on the thirteen patient outcomes. The preoperative management improved significantly. Eighteen of 24 process indicators improved, but only two improved significantly. Only for a few teams a geriatrician was an integral member of the treatment team. Discussion: Implementation of a care pathway improved compliance to evidence, but no significant effect on patient outcomes was found. The impact of the collaboration between surgeons and geriatricians on adherence to guidelines and patient outcomes should be studied. Trial registration: ClinicalTrials.gov: NCT00962910.